CONSTRUCTING THE ASSYRIAN SIEGE RAMP AT LACHISH: TEXTS, ICONOGRAPHY, ARCHAEOLOGY AND PHOTOGRAMMETRY. Issue 4 (14th October 2021) - Garfinkel, Yosef; Carroll, Jon W.; Pytlik, Michael; Mumcuoglu, Madeleine
Summary: This research examines the Assyrian siege ramp at Lachish, the only such known from the ancient Near East and the oldest in the world. The combination of different sources (texts, iconography and archaeology) enables us to reconstruct how this monumental war installation was erected. We used photogrammetric analysis, facilitated through small Unmanned Aerial System (sUAS) imagery, to digitally map the landscape and evaluate different potential scenarios with regard to the construction and use of the ramp.